Parent and Institution Communication In Creating Child Friendly Education - Latif Fadilah; Maulana Purwa Rimba (JELCre - Journal of Education and Learning Creativity, 2025)
Researchers promote child-friendly education in order to realize education that provides protection without violence, so that students feel comfortable, safe, and peaceful at school, allowing the learning process to run smoothly. The objectives of this study are (1) to analyze patterns of communication between parents and institutions in creating child-friendly education, (2) to analyze patterns of communication between parents and children in creating child-friendly education, and (3) to analyze problems in patterns of communication between parents, institutions, and children in realizing child-friendly education. In this study, the author used a qualitative approach and a multi-case study. The data collection techniques used included: 1) interviews, and 2) documentation. The data collected from these two techniques were analyzed from a single site and cross-case analysis. During data collection, the data obtained were tested using the triangulation method. The triangulation method used by the researcher used source triangulation as well as the methods of observation persistence and data validity. In this study, the researcher found several findings regarding the communication patterns of parents and madrasahs in creating child-friendly education at MI Hidayatus Sibyan and SDN Deyeng 2: (1) the communication patterns of parents with institutions in creating child-friendly education are interpersonal communication and group communication (2) Communication patterns